PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK - Gunawan, Juniati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to find out the influence of corporate social responsibility (CSR) and corporate governance (CG) with tax aggressiveness. Sample in this study is 42 with criterias: companies in Indonesia whichprovide sustainability reports in 2014 and obtain positif profit. Ã‚Â Analysis were conducted byusing multiple regression analysis. The result shows that CSR significantly influencetax aggresiveness. The more extensive CSRdisclosures, it seems that companies tend to be more aggressive in applyingtax. On the other hand, this study finds that corporate governance (CG) does not significantly influence tax aggressiveness. A good corporate governance score doesnot mean an effective corporate governance mechanism in combating un ethical behavior of managers in managing taxes.